A novel LC-MS/MS analysis of vitamin D metabolites in mice serum and hair: impact of diet and light exposure - Hakeem, Muhammad K.; Al-Menhali, Asma; Elangovan, Sampath K.; Shah, Iltaf (Frontiers in Endocrinology, 2025)
IntroductionNumerous physiological systems, such as the functioning of the immune system, bone health, and the regulation of expression of genes, depend critically on vitamin D. Considering the significance of vitamin D for health, it is critical to understand how it is metabolized and the factors that affect its levels.MethodsThe objective of this study was to develop and validate an LC-MS/MS method to examine the effects of light exposure and dietary vitamin D consumption on the levels of vitamin D and its metabolites in a mouse model under consistent growth conditions throughout the year. Serum and hair samples from mice were analyzed under various experimental conditions for vitamin D and its metabolites using liquid chromatography-tandem mass spectrometry (LC-MS/MS). The experimental conditions included a vitamin D-deficient diet, a vitamin D-standard diet, and changes in ambient light exposure ranging from complete darkness to a regular light-dark cycle.ResultsMice fed a standard vitamin D diet and exposed to a regular light-dark cycle exhibited significantly higher levels of 25OHD3 in both serum and hair, indicating the synergistic effect of dietary vitamin D intake and light exposure. Mice fed a standard vitamin D diet but kept in continuous darkness showed moderately elevated 25OHD3 levels, demonstrating the efficacy of dietary vitamin D in maintaining adequate levels despite the absence of light. Conversely, mice fed a vitamin D-deficient diet and housed in darkness displayed 25OHD3 levels below the limit of quantification, highlighting the combined detrimental effects of dietary deficiency and lack of light exposure.DiscussionThis study provides valuable insights into the complex interplay between dietary vitamin D intake, light exposure, and the regulation of vitamin D metabolism in mice. Moreover, our results underscore the potential implications for human health, suggesting the importance of adequate vitamin D intake and sunlight exposure in maintaining optimal vitamin D levels. Further research in this area has the potential to unveil additional factors influencing vitamin D metabolism, offering valuable insights into strategies for optimizing vitamin D levels in both animal models and human subjects.